2019
DOI: 10.3389/fnsyn.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Modulation of Visually-Guided Behavior

Abstract: Iontophoretic application of norepinephrine (NE) into the primary visual cortex (V1) in vivo reduces spontaneous and evoked activity, without changing the functional selectivity of cortical units. One possible consequence of this phenomenon is that adrenergic receptors (ARs) regulate the signal-to-noise ratio (SNR) of neural responses in this circuit. However, despite such strong inhibitory action of NE on neuronal firing patterns in V1, its specific action on visual behavior has not been studied. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
(137 reference statements)
0
11
0
Order By: Relevance
“…Variability at the circuit level is generated by many neurophysiological mechanisms that include the stochastic nature of synaptic transmission with relevant interactions across large neural populations and with distributed neuromodulation effects ( Dinstein et al, 2015 ; Trevino et al, 2019 ). Where exactly does the brain implement regulation for choice variability?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability at the circuit level is generated by many neurophysiological mechanisms that include the stochastic nature of synaptic transmission with relevant interactions across large neural populations and with distributed neuromodulation effects ( Dinstein et al, 2015 ; Trevino et al, 2019 ). Where exactly does the brain implement regulation for choice variability?…”
Section: Discussionmentioning
confidence: 99%
“…We characterized visual contrast responses by using static sine-wave gratings (0.04 cycles/degree) with multiple contrasts. Our screens were gamma-corrected to ensure linearly increasing intensity scales ( Trevino et al, 2019 ). We also tested the discriminative capacities of the mice by using a set of equiluminant images with variable structural similarity among them (SSIM).…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the topical administration of propranolol onto the surface of V1 improved behavioral performance of the VD task. Recently, two studies investigated β-AR modulation on perceptual visual ability (Mizuyama et al 2016 ; Treviño et al 2019 ). Treviño et al ( 2019 ) showed that the micro-infusion of isoproterenol, a β-AR agonist, in V1 decreased the visual discriminability of mice, indicating that the activation of β-AR in V1 worsens visual discriminability, which is consistent with our present study.…”
Section: Discussionmentioning
confidence: 99%
“…In vision, some studies reported that β-AR modulates perceptual visual sensitivity, but the effects were inconsistent. Treviño et al ( 2019 ) reported that the local administration of β-AR agonist on the primary visual cortex (V1) worsens the task performance of mice performing the two-alternative forced-choice (2-AFC) visual discrimination task in a water maze. On the other hand, Mizuyama et al ( 2016 ) showed that the systemic administration of a β-AR antagonist impairs the visual detectability of rats performing the 2-AFC visual detection (VD) task in an operant chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation